IL-36R signalling activates intestinal epithelial cells and fibroblasts and promotes mucosal healing in vivo. Issue 5 (18th January 2016) - Scheibe, Kristina; Backert, Ingo; Wirtz, Stefan; Hueber, Axel; Schett, Georg; Vieth, Michael; Probst, Hans Christian; Bopp, Tobias; Neurath, Markus F; Neufert, Clemens
Abstract : Objective: Interleukin (IL)-36R signalling plays a proinflammatory role in different organs including the skin, but the expression of IL-36R ligands and their molecular function in intestinal inflammation are largely unknown. Design: We studied the characteristics of IL-36R ligand expression in IBDs and experimental colitis. The functional role of IL-36R signalling in the intestine was addressed in experimental colitis and wound healing models in vivo by using mice with defective IL-36R signalling ( IL-36R −/−) or Myd88, neutralising anti-IL-36R antibodies, recombinant IL-36R ligands and RNA-seq genome expression analysis. Results: Expression of IL-36α and IL-36γ was significantly elevated in active human IBD and experimental colitis. While IL-36γ was predominantly detected in nuclei of the intestinal epithelium, IL-36α was mainly found in the cytoplasm of CD14 + inflammatory macrophages. Functional studies showed that defective IL-36R signalling causes high susceptibility to acute dextran sodium sulfate colitis and impairs wound healing. Mechanistically, IL-36R ligands released upon mucosal damage activated IL-36R + colonic fibroblasts via Myd88 thereby inducing expression of chemokines, granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-6. Moreover, they induced proliferation of intestinal epithelial cells (IECs) and expression of the antimicrobial protein lipocalin 2. Finally, treatment of experimental intestinal wounds with IL-36R ligands significantly accelerated mucosal healing in vivo. Conclusions: IL-36R signalling is activated upon intestinal damage, stimulates IECs and fibroblasts and drives mucosal healing. Modulation of the IL-36R pathway emerges as a potential therapeutic strategy for induction of mucosal healing in IBD.